Eskimofrau kehrt vom nächtlichen Fischen auf dem Eis zurück : [193-?] - Hettasch, Paul, 1873-1949. (2001)
Black and white photograph of an Inuit woman returning from ice fishing. Black and white photograph of an Inuit woman returning from ice fishing.